Fabrication of Unilateral Conductive and Transparent Polymer Thin Films Decorated With Nanomaterials for Flexible Electrodes - Taş, Mahmut; Cin, Zeynep İşlek; Şam Parmak, Ebru Devrim; Bedeloğlu, Ayşe (Wiley, 2018)
Recently, electrically conductive, flexible, and transparent nanocomposite thin films consisting of nanomaterials on insulating polymer layers are of particular interest to scientific and industrial experts and have promising applications in energy, electronic, and environment areas, due to their remarkable properties. In this study, nanomaterials including silver nanowires, reduced graphene oxide, and carbon nanotubes, and also, conducting polymer poly(3,4-ethylenedioxythiophene):polystyrene sulfonate were embedded onto insulating polyamide 6-based polymer layer to form unilateral (one-sided) conductive nanocomposite thin film with advanced optical, electrical, and mechanical properties. Spin coating technique was used to fabricate these flexible, conductive, and transparent thin film layers. Thin conductive films decorated with silver nanowires exhibited sufficiently low sheet resistance of 105 Omega/sq with a transparency of similar to 85%. The maximum measured stress and elongation was obtained as 2.24 N/mm(2) and 12.5%, respectively. (C) 2016 Society of Plastics Engineers
Keywords: [No Keywords]